'The fact they knew before I did upset me most': Essentialism and normativity in lesbian and gay youths' coming out stories. (June 2020) - Jones, Lucy
This article demonstrates, via discourse analysis of a group of young gay and lesbian people's coming out stories, the salience of essentialist ideologies on their identity construction. The study reveals underlying normative assumptions in the young people's narratives, including those associated with binary gender and innate sexual desire, which they employ in order to construct a culturally authentic sexual identity. Through close sociolinguistic analysis of interactions, it is shown how identity construction is directly influenced by broader ideologies. The analysis provides evidence of the continued prevalence of heteronormativity and homonormativity as key influences in young queer people's identity work.